Medición del ángulo de desviación en un pentaprisma usando un interferómetro de Sagnac - Jaramillo Núñez, A. (Revista Mexicana de Física, 2004)
A technique to measuring the error in the deviation angle of a pentaprism, which makes use of a Sagnac interferometer, is described. The beams of the interferometer are employed as reference beams in order to align the pentaprism. The deviation angle is measured with the aid of a reference flat attached to a goniometer mounting. Deviation angles with an error of 15 arcsec have been measured with a precision of 2 arcsec. The measurement precision can be improved substituting the goniometer for one of higher precision.